The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/aic.15225
|View full text |Cite
|
Sign up to set email alerts
|

Model‐based analysis of chemical‐looping combustion experiments. Part I: Structural identifiability of kinetic models for NiO reduction

Abstract: To guide the design of chemical-looping combustion (CLC) systems, the use of accurate models is crucial. The reduction kinetics between NiO and CH4 is uncertain, in regards to the most suitable kinetic mechanism and reaction network. A framework for structural identifiability analysis is developed and applied to evaluate the candidate kinetic models for the NiO-CH4 reaction. The identifiability of kinetic parameters of different model structures is analyzed and compared. Models that lack structural identifiabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…A1, were previously estimated from the nominal reduction experiment presented in Figure 4 of Part I. 24 The activation energies for R2-R4 were fixed to the reported values of Zhou et al 1 and for R5 to the reported value of Dueso et al 9 For the catalytic reactions, k Tref i was estimated in Part I, 24 keeping Ea i fixed to the reported values of Zhou et al 1 The results of the optimal experimental designs for model discrimination and parameter estimation are discussed. The posterior statistics of the parameter estimates are presented for each step of the framework.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A1, were previously estimated from the nominal reduction experiment presented in Figure 4 of Part I. 24 The activation energies for R2-R4 were fixed to the reported values of Zhou et al 1 and for R5 to the reported value of Dueso et al 9 For the catalytic reactions, k Tref i was estimated in Part I, 24 keeping Ea i fixed to the reported values of Zhou et al 1 The results of the optimal experimental designs for model discrimination and parameter estimation are discussed. The posterior statistics of the parameter estimates are presented for each step of the framework.…”
Section: Resultsmentioning
confidence: 99%
“…6, in which all models deemed identifiable in Part I 24 were assumed equally likely to be the true model. Equation 6 was solved over the four candidate models with bounds on the parameter values h Table 3.…”
Section: Design Of Experiments For Model Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ergun equation was used for the momentum balance. The reaction kinetics was derived from atmospheric‐ and high‐pressure gaseous CLC experiments that used supported Ni‐ and Cu‐based oxygen carriers . This model was developed by using gPROMS and was used successfully for the prediction of CLC data over a range of operating pressures, temperatures, and fuel compositions.…”
Section: Description Of Modelsmentioning
confidence: 99%